Vaccination and COVID-19: impact on long-COVID - Guimarães, Gustavo N.; Brunetti, Natália S.; De Lima, Dieila G.; Proenca-Modena, José Luiz; Farias, Alessandro S. (Frontiers in Immunology, 2025)
Long- and post-COVID-19 syndromes have emerged as a significant global health challenge, with millions of individuals experiencing persistent or the development of new symptoms after a long period of an initial SARS-CoV-2 infection. These symptoms are multisystemic and may indicate changes in the respiratory, neurological, cardiovascular and gastrointestinal systems, in addition to prolonged fatigue. Vaccination has played a crucial role in reducing severe disease and mortality, but the impact of the different vaccine combinations on the development and resolution of Long COVID remains a topic of debate. This review synthesizes current evidence on how different vaccine platforms, dosing strategies and booster doses influence the immunological response, protection, incidence, severity, and persistence of Long COVID symptoms. We discuss key immunological mechanisms by which vaccination may modulate and protect post-COVID syndrome outcomes, including its effects on viral clearance, immune response reprogramming, inflammation, and autoimmunity, seeking to combat misinformation and concepts spread by fake news. The review also highlights controversies and research gaps, such as variability in vaccine response among different populations and the role in the selection of more transmissible and virulent SARS-CoV-2 variants, as well as the potential differences between vaccine-induced and infection-induced immunity, and the role of pre-existing immune conditions in this scenario.